Capacity Building Needs of Artisanal Fisherfolks in North Central, Nigeria - Ifabiyi , J. O. (Diyala Agricultural Sciences Journal, 2022)
The study analyzed the capacity building needs of artisanal fisherfolks in North Central, Nigeria. The Data were collected with the use of a questionnaire and analysed using frequency, percentages, mean score and Correlation. The results showed that about 99.2% of the fishers were male and the mean age of the fishers was 43.9ears. The mean years of experience were 24.3. The mean quantity of catch per day was 17.9 Kg and 6 persons was the average household size. About 47.33 % of the respondents has a high knowledge level on improved fishing practices. The fisherfolks required capacity building in handling and transportation of captured fish (x ̅=6.59), use and repair of nets, cages and traps (mean=6.29), use and maintenance of multiple hooks on a line (x ̅=6.71), canoe use and maintenance (x ̅=6.74), use of chorkor smoker (x ̅=6.68), fish marketing and distribution (x ̅=6.65), credit acquisition (x ̅=5.92), maintaining personal and environmental health hygiene (x ̅=6.0) and local weather forecasting (x ̅=6.32). The highest ranked constraints affecting artisanal fishing practices were the high cost of fishing inputs and inadequate access to credit facilities (x ̅=2.72). The study therefore recommends the provision of training in the identified areas of capacity building needs and the provision of more frequent and effective extension services to the fisherfolks.